Electrodeionization of li-containing solutions using ion exchange material based on tio2-mno2 - Chaban, Mariya; Rozhdestvenska, Lyudmyla; Dzyazko, Yulia (My University, 2018)
In this work the problem of selective extraction of Li+ ions from combined solutions by electromembrane method is being solved. Sorbent based on lithium-substituted titanium manganese oxide was used. It is established that the function of the sorbent in the membrane system is reduced to the turbulization of the solution flow, but under the influence of alkalization of the solution near the surface of the sorbent granules, its sorption capacity increases with an increase in voltage from 3 to 20 V.
Keywords: electrodialysis; electrodionization; ion-exchange membrane; lithium-titanium-manganese spinel; електродіаліз; електродеіонізація; іонообмінна мембрана; літій-титан-марганцева шпінель; электродиализ; электродеионизация, ионообменная мембрана; литий-титан-марганцевая шпинель